Numerical and Experimental Analysis of the Shear Behavior of Ultrahigh-Performance Concrete Construction Joints - Hyun-O. Jang; Han-Seung Lee; Keunhee Cho; Jinkyu Kim (Advances in Materials Science and Engineering)
Shear performance of plain UHPC (ultrahigh-performance concrete) construction joints is studied in both experimental and analytical ways. In push-off tests, three different contact surfaces of the construction joint were considered, while the case without any joint was provided for the reference. Test results indicate that the geometry of contact surfaces greatly affects shear performance of the construction joint. With simplifying structural behavior of contact surfaces and UHPC substrate, the finite-element analysis model is developed for every case studied by utilizing the ABAQUS software and validated against the test results. Agreement between experimental and numerical simulation results is excellent especially in terms of displacement, strength, and failure mechanism. It is expected that the present work provides a basis for further study on reinforced UHPC construction joints.